Underlay tympanoplasty with tunneling and placement of graft in anterior canal wall - Ganguly, SN; Reddy, NS; Shrestha, A; Acharya, A; Battarai, B (Journal of College of Medical Sciences-Nepal, 2012)
Tympanoplasty is one of the commonest surgical procedures done by ENT Surgeons. Though it has a long history of about six decades, various techniques have been advocated. Today most widely used technique is underlay. Overlay technique is reserved for total perforation. A modification of the underlay technique with anterior tunneling and placement of graft in anterior canal wall was tried and evaluated. Cases were selected from patients attending CMS-TH, Bharatpur. Seventy (70) cases were included and results were evaluated. Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 44-47 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6740